SPONTANEOUS ADVERSE DRUG REACTION REPORTING IN A TERTIARY CARE HOSPITAL IN CALICUT - Sundaran, Siraj; S, Abhijith P; Alex, Aleena; Krishnan, Amrutha; Jacob, Angel Tisa; Babu, G; Balakrishnan, Sudeep (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The study was conducted to assess the adverse drug reactions (ADRs) reported in a tertiary care hospital in Calicut. Methods: Spontaneous ADR reporting method was followed for the study. The ADRs reported by the health-care professionals, or the patients were confirmed with the physician-in-charge. Further, the assessments of type, severity, and preventability of reported ADRs were done using Wills and Brown classification, modified Schumock and Thornton severity scale, and modified Hartwig and Siegel preventability scale. Results: A total of 30 ADRs were reported. A study found that the incidence of ADRs was more in males (1.14%) when compared to females (0.79%). Geriatric patients showed more incidences of ADRs (1.04%) when compared to pediatrics (0.69%) and adults (1.02%). More number of ADRs was associated with antibiotics (23.33%) and anticonvulsants (23.33%) than another category of drugs. Based on type or mechanism involved 80% of ADRs were pharmacologically related (Augmented) ADRs. Severity assessment showed that 50% were mild, 46.67% were moderate, and 3.33% were severe. Assessment of preventability showed that 63.33% of ADRs were not preventable, 30% were preventable, and 6.67% were probably preventable. Conclusion: The study was useful in finding the age category and drugs that were more prone to ADRs. This will render precautions and monitoring in the future. The importance of ADR monitoring unit and aid of clinical pharmacist in the monitoring and assessment were very well considered during the study.